KERJASAMA UNITED NATIONS WORLD TOURISM ORGANIZATION (UNWTO) DENGAN INDONESIA DALAM PENGEMBANGAN SEKTOR PARIWISATA DI PANGANDARAN, JAWA BARAT TAHUN 2011-2013 - Dani Angraini; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This reserach describes the collaboration between UNWTO (United Nations World Tourism Organization) and Indonesia within developing tourism sector in Pangandaran 2011-2013. Tourism sector is an important component of the Indonesia economy, and Pangandaran is one of the popular tourism destinations in West Java that contribute in Indonesia economy. However, due to the tsunami disaster in 2006 severely effect within tourism in Pangandaran. The purpose of this research is to explain the STREAM (Sustainable Tourism through Energy Efficiency with Adaptation and Mitigation Measures) project as a form of collaboration between UNWTO and Indonesia in developing the tourism sector in Pangandaran to revitalizing the tourism area.This research uses qualitative methods with techniques of writing a literature review through the secondary data which are already available in the literature, books, journals and website searches. This research also uses pluralism perspective, international organization theory and collaboration theory to explain collaborating between UNWTO and Indonesia.The result of this research indicates that the STREAM project has made Pangandaran as tourism areas that are resistant to the climate change and able to increase tourist arrivals, both local and foreign. This research also shows the successful of the STREAM project. One of the success factors of this project is the involvement of the local community and surrounding communities during the project was implemented. The STREAM project in Pangandaran is being implemented by UNWTO together with the Indonesia Ministry of Tourism and Creative Economy. The project is also part of the International Climate Initiative (ICI) of the German Federal Ministry for the Environment, Nature Conservation and Nuclear Safety.Keywords: UNWTO, Tourism, STREAM Project, Climate Change